Anti‐Ambipolar Transport with Large Electrical Modulation in 2D Heterostructured Devices. Issue 24 (18th April 2019) - Cheng, Ruiqing; Yin, Lei; Wang, Feng; Wang, Zhenxing; Wang, Junjun; Wen, Yao; Huang, Wenhao; Sendeku, Marshet Getaye; Feng, Liping; Liu, Yufang; He, Jun
Abstract: Van der Waals materials and their heterostructures provide a versatile platform to explore new device architectures and functionalities beyond conventional semiconductors. Of particular interest is anti‐ambipolar behavior, which holds potentials for various digital electronic applications. However, most of the previously conducted studies are focused on hetero‐ or homo‐ p–n junctions, which suffer from a weak electrical modulation. Here, the anti‐ambipolar transport behavior and negative transconductance of MoTe2 transistors are reported using a graphene/h‐BN floating‐gate structure to dynamically modulate the conduction polarity. Due to the asymmetric electrical field regulating effect on the recombination and diffusion currents, the anti‐ambipolar transport and negative transconductance feature can be systematically controlled. Consequently, the device shows an unprecedented peak resistance modulation factor (≈5 × 10 3 ), and effective photoexcitation modulation with distinct threshold voltage shift and large photo on/off ratio (≈10 4 ). Utilizing this large modulation effect, the voltage‐transfer characteristics of an inverter circuit variant are further studied and its applications in Schmitt triggers and multivalue output are further explored. These properties, in addition to their proven nonvolatile storage, suggest that such 2D heterostructured devices display promising perspectives toward future logic applications. Abstract : A novel van der Waals heterostructured device with very large electrical modulation and nonvolatile properties is demonstrated. The corresponding anti‐ambipolar transport and negative transconductance feature can be well controlled and can be applied in logic circuits including Schmitt triggers and multivalue output, providing a new direction for designing future electronics devices.